Manganese Poisoning in Alagille's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
An 8 year old girl with Alagille's syndrome who developed dystonia secondary to manganese toxicity is reported from the Pediatric Department, Hershey Medical Center, Hershey, PA.